Utilization of Coconut Shell Charcoal for Grounding Resistance Reduction Using Plate Electrodes - Yusran Moha; Taufiq Ismail Yusuf; Ade Irawaty Tolago (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
The grounding system is an essential component of electrical protection systems, requiring low resistance values to ensure the safety of equipment and personnel. The grounding resistance is influenced by several factors, including soil type, soil moisture, temperature, as well as the structure and characteristics of the soil at the installation site. One method that can be applied to reduce grounding resistance is the use of additional materials such as coconut shell charcoal. This study aims to analyze the effect of adding coconut shell charcoal on grounding resistance using square plate electrodes. The testing was conducted over a period of 15 days with variations in electrode size, namely 40 cm and 60 cm, installed at a depth of 80 cm. The results indicate that the addition of coconut shell charcoal significantly reduces grounding resistance. The resistance value decreased from 43.4 Ω to 10 Ω when using a 40 cm electrode and from 21.5 Ω to 7.6 Ω when using a 60 cm electrode on the 15th day. The percentage reduction in resistance reached 77%. Furthermore, the use of larger electrodes resulted in lower resistance values. These results demonstrate that coconut shell charcoal is effective in improving the performance of grounding systems.